Using Mixed Reality and Natural interaction in Cultural Heritage Applications (Informatica, 2016)
In this paper, we present a general architecture for Mixed Reality applications. The proposed solution has been developed in order to provide a useful instrument to develop Cultural Heritage applications. During the design of the system, particular attention was given to intangible knowledge, such as manual activities, performing arts, lost civilizations habits, representing a particular heritage poorly addressed by previous studies. The system aims at providing an easy and engaging infrastructure to develop immersive application to be used for communication / dissemination and education purposes. The proposed architecture exploits Natural User Interfaces solutions as interaction metaphor between the Virtual Environment and the user. Natural interaction in fact provides high sense of presence and immersion to the user, improving the user engagement and fostering the learning process.The paper presents also two case studies, where two different applications aimed at teaching and disseminating crafts knowledge, in particular printmaking and weaving, have been developed on top of the presented architecture.